The Influence of Tourist Attractions and Facilities on the Decision to Visit Sipinsur Tourist Destinations, Humbang Hasundutan Regency, North Sumatra - Simamora, Monica Saiuli; Safarudin, Safarudin (CV. Civiliza Publishing, 2025)
The declining interest of tourists in visiting the Sipinsur Geosite tourist destination in Humbang Hasundutan Regency has emerged as an issue requiring thorough investigation. Despite the area's considerable natural appeal—such as panoramic views of Lake Toba and the surrounding pine forest—several issues related to the availability and quality of supporting facilities remain, including unsanitary public restrooms, a lack of waste disposal infrastructure, and limited shelter amenities. This study aims to analyze the influence of tourist attractions and facilities on tourists’ visiting decisions to the Sipinsur destination. A quantitative approach was employed, utilizing a survey method with questionnaires distributed to 96 respondents who had visited or were currently visiting Sipinsur. Data were analyzed using multiple linear regression to assess both partial and simultaneous effects between variables. The findings reveal that both tourist attraction and facility variables have a positive and significant effect on visiting decisions, both individually and collectively. Tourist attraction was found to have a more dominant influence, though both factors significantly contribute to shaping tourists’ decisions. These findings offer strategic implications for destination managers and stakeholders in the effort to develop a tourism site that emphasizes the sustainable enhancement of visitor experiences.